Atypical white matter microstructure in left-handed individuals. Issue 3 (4th May 2017) - McKay, Nicole S.; Iwabuchi, Sarina J.; Häberling, Isabelle S.; Corballis, Michael C.; Kirk, Ian J.
ABSTRACT: Information regarding anatomical connectivity in the human brain can be gathered using diffusion tensor imaging (DTI). Fractional anisotropy (FA) is the most commonly derived value, and reflects how strongly directional are the underlying tracts. Differences in FA are thus associated with differences in the underlying microstructure of the brain. The relationships between these differences in microstructure and functional differences in corresponding regions have also been examined. Previous studies have found an effect of handedness on functional lateralization in the brain and corresponding microstructural differences. Here, using tract-based spatial statistics to analyse DTI-derived FA values, we further investigated the structural white matter architecture in the brains of right- and left-handed males. We found significantly higher FA values for left-handed, relatively to right-handed, individuals, in all major lobes, and in the corpus callosum. In support of previous suggestions, we find that there is a difference in the microstructure of white matter in left- and right-handed males that could underpin reduced lateralization of function in left-handed individuals.